Associations between Parental Concerns about Preschoolers' Weight and Eating and Parental Feeding Practices: Results from Analyses of the Child Eating Behavior Questionnaire, the Child Feeding Questionnaire, and the Lifestyle Behavior Checklist. - Anna Ek; Kimmo Sorjonen; Karin Eli; Louise Lindberg; Jonna Nyman; Claude Marcus; Paulina Nowicka (PLoS ONE, 2016)
Insight into parents' perceptions of their children's eating behaviors is crucial for the development of successful childhood obesity programs. However, links between children's eating behaviors and parental feeding practices and concerns have yet to be established. This study aims to examine associations between parental perceptions of preschoolers' eating behaviors and parental feeding practices. First, it tests the original 8-factor structure of the Child Eating Behavior Questionnaire (CEBQ). Second, it examines the associations with parental feeding practices, measured with the Child Feeding Questionnaire (CFQ).Questionnaires were sent to parents from 25 schools/preschools in Stockholm, Sweden and to parents starting a childhood obesity intervention. The CEBQ factor structure was tested with confirmatory factor analysis (CFA). Associations between CEBQ subscales Food approach and Food avoidance and CFQ factors Restriction, Pressure to eat and Monitoring were examined with structural equation modelling (SEM), adjusting for child and parental characteristics, and parental confidence, measured with the Lifestyle Behavior Checklist (LBC). CFQ Concern for child weight and Perceived responsibility for child eating were used as mediators.478 parents completed the questionnaires (children: 52% girls, mean age 5.5 years, 20% overweight/obese). A modified 8-factor structure showed an acceptable fit (TLI = 0.91, CFI = 0.92, RMSEA = 0.05 and SRMR = 0.06) after dropping one item and allowing three pairs of error terms to correlate. The SEM model demonstrated that Food approach had a weak direct effect on Restriction, but a moderate (β = 0.30) indirect effect via Concern, resulting in a substantial total effect (β = 0.37). Food avoidance had a strong positive effect on Pressure to eat (β = 0.71).The CEBQ is a valid instrument for assessing parental perceptions of preschoolers' eating behaviors. Parental pressure to eat was strongly associated with children's food avoidance. Parental restriction, however, was more strongly associated with parents' concerns about their children's weights than with children's food approach. This suggests that childhood obesity interventions should address parents' perceptions of healthy weight alongside perceptions of healthy eating.